Trends in Corticosteroid Prescriptions for Ulcerative Colitis and Factors Associated with Long-Term Corticosteroid Use: Analysis Using Japanese Claims Data from 2006 to 2016. (26th August 2020) - Matsuoka, Katsuyoshi; Igarashi, Ataru; Sato, Noriko; Isono, Yuri; Gouda, Maki; Iwasaki, Katsuhiko; Shoji, Ayako; Hisamatsu, Tadakazu
Abstract: Background and Aims: Recent treatment guidelines for ulcerative colitis [UC] do not recommend long-term corticosteroid [CS] use. The present study aimed to capture the changes in CS use from 2006 to 2016 and to identify factors associated with long-term CS use after 2014, when the first two anti-tumour necrosis factor antibodies [infliximab and adalimumab] became available. Methods: A retrospective study using the JMDC Claims Database included UC patients who initiated UC medications in any year from January 2006 to December 2016, or after January 2014, who were under continuous observation from 6 months before to 12 months after initiation. Patients with Crohn's disease before initiation and those prescribed <8 days of CSs were excluded. Results: Among 7907 UC patients who initiated UC medications within the study period, 1555 were prescribed CSs. The proportion of patients using CSs in each year decreased from 2011 as use of thiopurines and biologics increased. The proportion of patients with a starting dose ≥30 mg/day of CSs and patients continuing CSs for <90 days increased from 2011, reaching 49.1% and 41.0%, respectively, in 2016. However, even in 2016, 34.3% continued to use CSs for ≥180 days. Among 1230 patients with CS use after January 2014, low initial CS dose [<10 mg/day] was most strongly associated with long-term CS use [≥180 days]. Conclusions: CS use became more appropriate as use of thiopurine and biologics increased, although there were still many cases of inappropriate use. Long-term CS use was most strongly associated with low initial doses of CSs.